Analysis of the Influence Mass Variations of Banana STEM Fibres with Polypropylene (PP) Matrix on Accoustic and Porosity Properties - Santika, Viera Alvio; Darvina, Yenni; Ratnawulan, Ratnawulan; Jhora, Fadhila Ulfa (Journal of Experimental and Applied Physics, 2024)
Noise pollution is sound that you do not want to hear or is known as noise. If people hears loud noises continuously, it can disrupt hearing function. Therefore, it is necessary to have noise control by making an acoustic material that will be coated on the room's walls. A cheap and environmentally friendly alternative material is using banana stem waste from the fibre taken and with polypropylene as a fibre binder. This research aims to determine the effect of variations in the mass composition of banana stem fibre with the matrix polypropylene on the value of the acoustic properties and porosity, and determine the relationship between porosity with acoustic properties. Characteristics of the acoustics that will be measured are sound absorption coefficient, sound reflection coefficient, and transmission loss. The method used is using a characterizaton tool with one microphone impedance tube and porosity test tool with a digital scale. Acoustic material is made by varying the mass percentage in the ratio of polypropylene and midrib fibre banana, namely 90%:10%; 85%:15%; 80%:20%; 75%:25%; and 70%:30%. Based on the research results, it is known that the more fibre composition in the composite, the sound absorption coefficient values, transmission loss values, and porosity values were higher produced, but the resulting sound reflection coefficient value was lower. Then, the relationship between porosity with acoustic properties was that the higher porosity value, the resulting sound absorption coefficient and transmission loss value are higher too. However, the resulting sound reflection coefficient value was getting lower.